2020
DOI: 10.1080/09168451.2020.1770572
|View full text |Cite
|
Sign up to set email alerts
|

Influence of freeze-drying and spray-drying preservation methods on survivability rate of different types of protectants encapsulated Lactobacillus acidophilus FTDC 3081

Abstract: The aims of this study were to compare the effectiveness of different drying methods and to investigate the effects of adding a series of individual protectant such as skim milk, sucrose, maltodextrin, and corn starch for preserving Lactobacillus acidophilus FTDC 3081 cells during spray and freeze-drying and storage at different temperatures. Results showed a remarkable high survival rate of 70–80% immediately after spray- and freeze-drying in which the cell viability retained at the range of 109 to 1010 CFU/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 23 publications
2
3
0
3
Order By: Relevance
“…These results are comparable with those obtained by Tang et al [ 46 ], who observed reductions in cell viability from 13.01 log CFU to 8.71 ± 0.22 (66.95% cell survival) and to 7.88 ± 0.27 (60.57% cell survival) in freeze-dried Lactobacillus acidophilus FTDC 3081 treated with skim milk as a cryoprotectant stored for 30 days at temperatures of 25 °C and 40 °C, respectively. Among the factors that favor the cell viability of lactobacilli during storage are the use of cryoprotectants and antioxidants, since they protect it from cell stress caused by the temperature process, as well as from oxygen and environmental humidity, among other factors [ 47 , 48 ].…”
Section: Resultssupporting
confidence: 90%
“…These results are comparable with those obtained by Tang et al [ 46 ], who observed reductions in cell viability from 13.01 log CFU to 8.71 ± 0.22 (66.95% cell survival) and to 7.88 ± 0.27 (60.57% cell survival) in freeze-dried Lactobacillus acidophilus FTDC 3081 treated with skim milk as a cryoprotectant stored for 30 days at temperatures of 25 °C and 40 °C, respectively. Among the factors that favor the cell viability of lactobacilli during storage are the use of cryoprotectants and antioxidants, since they protect it from cell stress caused by the temperature process, as well as from oxygen and environmental humidity, among other factors [ 47 , 48 ].…”
Section: Resultssupporting
confidence: 90%
“…Using a combination of skimmed milk and MgSO4 for B. subtilis strain CPA-8 formulation development resulted in a good bacteria survival around 28 -30 % [16]. Lactobacillus acidophilus FTDC 3081 using maltodextrin as a protective agent had the highest viability in both spray drying and freeze-drying processes, which can reduce the absorption of moisture and prevent stickiness during storage [32]. Sodium alginate is a film-forming polymer that can protect cells and also improve the release rate.…”
Section: Preparation Of Bioformulation By Spray Drying and Viability ...mentioning
confidence: 99%
“…Bahan Penyalut yang Sesuai untuk BAL Maltodekstrin dan susu skim adalah bahan penyalut yang biasa digunakan untuk menyalut probiotik (Nocianitri, Sujaya and Ramona, 2019) yang diketahui dapat menghambat penurunan viabilitas BAL. Viabilitas BAL dengan bahan penyalut maltodekstrin menurun sebesar 1,87 log CFU/g setelah spray drying dan 1,59 log CFU/g setelah freeze drying (Sohail et al, 2013), sedangkan viabilitas BAL dengan bahan penyalut susu skim rata-rata menurun sebesar 3,72 log CFU/mL setelah spray drying dan 2,74 log CFU/mL setelah freeze drying (Tang et al, 2020).…”
Section: Hasil Penelitian Dan Pembahasan Viabilitas Bal Setelah Prose...unclassified
“…Tabel 2 dan 3 menunjukkan bahwa selama penyimpanan 30 hari pada suhu 40 °C, viabilitas BAL yang dienkapsulasi dengan bahan penyalut maltodekstrin atau susu skim mengalami penurunan viabilitas yang lebih besar dibandingkan dengan penyimpanan pada suhu 4 dan 25 °C, baik itu mikroenkapsulasi BAL hasil spray drying maupun freeze drying (Tang et al, 2020). Hal tersebut dapat terjadi karena suhu penyimpanan yang rendah dapat memperlambat terjadinya reaksi merugikan dari mikroorganisme, seperti menghambat oksidasi lipid membran plasma yang dibentuk oleh fosfolipid tak jenuh, sedangkan suhu penyimpanan yang tinggi menyebabkan laju degradasi yang lebih tinggi (Wang et al, 2019).…”
Section: Hasil Penelitian Dan Pembahasan Viabilitas Bal Setelah Prose...unclassified
See 1 more Smart Citation